Factors of customers' intention to use personal financing : comparison between conventional and islamic / Nor Syamila Jamaludin - Jamaludin, Nor Syamila (Faculty of Business Management, 2017)
One of the factors that lead to bankruptcy among adults is personal loan. The high interest rate will burden the youngest to make repayment loan for every month. Moreover, they assume a personal loan is the only option for those who have poor credit or do not own any assets that can be used as collateral to make secure loan (Ibrahim, 2012). Due to high cost of living, they have no option unless make personal financing with financial institutions. Even though, they have option to make personal financing with Islamic banks, which does not charge high interest but there have certain groups of people who are still make conventional personal financing. This research had going to perform the comparison between conventional and Islamic personal financing. The purpose of this study is to identify the factors of customer's intention to use personal financing in Selangor. There are 200 sets of questionnaires have been distributed to customers of personal financing. The data have be analysis by SPSS software. A few of analysis have been done to evaluate the data such as frequency, reliability analysis, descriptive analysis, correlation analysis and multiple regression analysis. The findings shown attitude and pricing have significant relationship with customers' intention to use Islamic personal financing meanwhile attitude and social influence have significant relationship with customers' intention to use conventional personal financing.